Media in education in the freirian perspective: Challenges and possibilities - Tomelin, Nilton Bruno; Rausch, Rita Buzzi (Seven Editora, 2023)
The presence of the media in Education is not exactly new, as is the need to educate oneself through dialogue. Paulo Freire understood that Education and media are related, although there are numerous challenges for each one to assume their role in the task of forming human beings, drawing possibilities for critical and politicized teaching. In this sense, the objective of this investigation was to identify the challenges and possibilities of the insertion of the media in Education from the Freirean perspective to the constitution of the critical/political practice of teaching. The practice of problematizing education, in this sense, is pointed out as an important way to sustain the relationship between the media and Education. This is a qualitative and bibliographical research in which the works of Freire (1980, 1982, 1995, 1996a, 1996b, 1997a, 1997b, 1999a, 1999b, 2000a, 2000b, 2001, and 2011) were particularly analyzed. Some challenges are pointed out, among which are: the concentration of media power, the recognition of the supremacy of the human over the instrumental, indispensability of the use of media in Education. As for the possibilities, it is worth mentioning: the dynamization of the pedagogical process; the perception of the importance of the teaching figure; the politicization of teachers; the indispensability of the figure of the teacher in human formation. Thus, it establishes an important role of the media for the Education of the future to be conceived as something to be built. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-001